Coping with stressful competitions in elite alpine skiing - Magelssen, C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Elite alpine ski racers` ability to cope with stressful competitions seems to fluctuate from one race to another. In light of the Cognitive Activation Theory of Stress (CATS; Ursin & Eriksen, 2004), this fluctuation could be attributed to variation in Response Outcome Expectancies (ROE), with positive ROE when a racer is able to cope and no ROE (helplessness) or a negative ROE (hopelessness) when not able to cope. Alternatively, coping effectiveness approaches (Nicholls, 2010) explain this fluctuation in terms of effective and ineffective coping strategies. Owing to these vast differences, this study took a first-hand perspective and asked skiers themselves to describe what happens when they manage to cope with a stressful competition and when they are not able to cope.